Faktor Sosial Ekonomi Masyarakat dan Pola Konsumsi Minyak Goreng di Kelurahan Pulubala Kota Gorontalo - Chusnul Islamiyati Jusuf; Ria Indriani; Echan Adam (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The Government’s policy to increase the price of cooking oil has changed the pattern of people’s consumption of cooking oil and has impacted the types of products people are interested in. This study aims to analyze the consumption patterns of packaged cooking oil during rising prices and the relationship between socio-economic factors and the amount of packaged cooking oil consumption in Gorontalo City. The research was conducted from October to December 2022, when there was a response to the policy of increasing cooking oil prices. The selected sample is 90 households. Data were analyzed using Descriptive and PPM-CorrelationStatisticsAnalysis.The results of the study show that there is a change in the consumption pattern of cooking oil when there is an increase in prices, where the public's consumption of retail cooking oil tends to decrease and switch to cooking oil products subsidized by the Government. Most people consume 'Minyakita' products because of their affordable price and better quality. The results of the PPM-Correlation statistical test also show a significant relationship between income and family members with the amount of packaged cooking oil consumed, where lower pay and fewer family members in the household further reduce the consumption of packaged cooking oil. Meanwhile, the Age and Education level of the respondents did not have a significant relationship with the amount of packaged cooking oil consumed when the price of cooking oil rose.